Features of cabbage moth development (Mamestra brassicae L.) on the cultivated cabbage in the Poltava area - Пономаренко, С. В. (Scientific Progress & Innovations, 2012)
The cultivated cabbage occupies a leading place among vegetables. In all regions of growing it is annually damaged by pests, as a result without effective measures harvest loss is 30–70 %. Complex of pests cruciferous has about 300 kinds, among them there are ten kinds of specialized pests. The problem of features of development and long-term seasonal dynamics of quantity of representative of cultivated cabbage leaf beetles thar is cabbage moth in the Poltava area has been investigated.